2012
DOI: 10.1002/ptr.4608
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity‐guided Fractionation of Phyllanthus orbicularis and Identification of the Principal Anti HSV‐2 Compounds

Abstract: The antiherpes virus properties of Phyllanthus orbicularis Kunth, a Cuban-endemic medicinal plant, have been reported previously but data on its phytochemical profile and identification of antiviral metabolites as well as their mechanisms of action are still lacking. In this work, a bioactivity-guided phytochemical analysis was performed in order to isolate anti HSV-2 compounds. P. orbicularis contained mainly phenolic acids derivatives and flavonoids. The antiviral effects were attributed to (-)-epicatechin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
(29 reference statements)
0
22
0
1
Order By: Relevance
“…It has been proposed that the presence of sugar in the flavonoid skeleton improves the antiviral activity when compared to the kaempferol aglycone. However, in another study, kaempferol 3‐ O ‐rutinoside did not exhibit any antiherpetic activity …”
Section: Resultsmentioning
confidence: 89%
“…It has been proposed that the presence of sugar in the flavonoid skeleton improves the antiviral activity when compared to the kaempferol aglycone. However, in another study, kaempferol 3‐ O ‐rutinoside did not exhibit any antiherpetic activity …”
Section: Resultsmentioning
confidence: 89%
“…However, despite the extensive antiviral studies that was carried out on Phyllanthus species, only P. urinaria , P. emblica and P. orbicularis have been tested for their antiviral activities against HSV, whereas other species such as P. amarus and P. niruri that demonstrate potent antiviral activity against HIV and HBV have not been tested against HSV 20, 26, 31. Hence this study would be the first preliminary study that determine and compare the anti-HSV activities of the four Phyllanthus species, namely P. amarus , P. niruri , P. urinaria and P. watsonii that can be locally found in Malaysia by using quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Phyllanthus niruri was first shown to inhibit the hepatitis B virus (HBV) and woodchuck hepatitis virus (WHV) both in vitro and in vivo by Venkateswaran et al 17. Antiviral testing was carried out using different members of the Phyllanthus family and various species members such as the P. amarus , P. niruri , P. urinaria and P. orbicularis have reported to demonstrate potential inhibitory effect against broad spectrum of viruses, such as the hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV) and herpes simplex virus (HSV) 18-20. Apart from the reported antiviral activities, other reported activities include anti-cancer 21, 22, hepatoprotective 23, lipid lowering 24 and blood glucose lowering activity 25, suggesting the broad spectrum activities in this plant species and as a potential drug discovery candidate.…”
Section: Introductionmentioning
confidence: 99%
“…48) This result could provide a pharmacological basis to inhibit PRRSV replication. 27) In addition, many other plant-derived substances from TMPs such as Murraya koenigii, Erythrina caffra, Corydalis saxicola, Larrea tridentate, Holarrhena antidysenterica, and Melampyrum arvense exerted antiviral, 49,50) antibacterial, 51,52) and antiprotozoal 53,54) activities.…”
Section: Major Pharmacological Activitiesmentioning
confidence: 99%
“…65) It is not surprising that SAR studies provide information (41)(42)(43)(44) showed that a prenyl group at C-4 plays an important role in the inhibitory activity. SAR studies on a new nitrocontaining tetrahydroprotoberberine (45) and five isoquinoline alkaloids (46)(47)(48)(49)(50) showed that nitro substituents at ring A improve anti-AchE activity. Comparing the antimicrobial activity of 48, 49, and 51, the SAR results showed that the substituent group on phenyl rings C2 and C3 as well as methylenedioxy improves antimicrobial activity more markedly than methoxyl.…”
Section: Sar Studies On the Pharmacological Activity Ofmentioning
confidence: 99%